Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/jnr.20786
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐apoptotic role of c‐Jun in NMDA‐induced neurotoxicity in the rat retina

Abstract: We examined the role of c-Jun on N-methyl-D-aspartate (NMDA)-induced neurotoxicity in the rat retina. An increase in c-Jun mRNA, c-Jun protein and phosphorylated c-Jun (p-c-Jun) levels in the retina was detected 3 hr after intravitreal injection of NMDA (20 nmol). These levels peaked after 12 hr, and then returned to their control levels by 24 hr. c-Jun and p-c-Jun immunoreactivities were observed in the retinal ganglion cell layer (RGCL), especially in retinal ganglion cells (RGCs), and in the inner nuclear l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Protection in these studies has been attributed to a reduction in phosphorylated JUN (pJUN) leading to an attenuation of JUN/AP-1 activity. JUN is known to be upregulated after various axonal and/or glaucoma relevant insults in RGCs (Isenmann and Bahr, 1997; Levkovitch-Verbin et al, 2005; Munemasa et al, 2006). To determine if JNK could be mediating RGC death by a JUN dependent pathway after axonal injury, activation of JUN (as measured by phosphorylation of Ser-63) was assessed in wildtype and Jnk mutant mice after CONC.…”
Section: Resultsmentioning
confidence: 99%
“…Protection in these studies has been attributed to a reduction in phosphorylated JUN (pJUN) leading to an attenuation of JUN/AP-1 activity. JUN is known to be upregulated after various axonal and/or glaucoma relevant insults in RGCs (Isenmann and Bahr, 1997; Levkovitch-Verbin et al, 2005; Munemasa et al, 2006). To determine if JNK could be mediating RGC death by a JUN dependent pathway after axonal injury, activation of JUN (as measured by phosphorylation of Ser-63) was assessed in wildtype and Jnk mutant mice after CONC.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that axotomy of the optic nerve causes a change in redox status, indicating an increase in Trx1 and Trx2 levels in isolated RGCs. Overexpression of Trx1 and Trx2 prevents axotomy-induced RGC loss, indicating the critical role of the redox status in axotomized RGC degeneration (Munemasa et al, 2006). …”
Section: Cell Body Injurymentioning
confidence: 99%
“…Intracellular Ca 2+ influx also affects mitochondrial activity, such as the release of cytochrome C and ROS, and results in the activation of several apoptotic pathways. Our previous studies on the downstream intracellular Ca 2+ influx led us to propose that the activation of proapoptotic molecules, such as NF-κB p65 and p38, c-Jun N -terminal kinase (JNK), and c-Jun, plays a role in NMDA-induced neurotoxicity (Kitaoka et al, 2004; Munemasa et al, 2005, 2006; Takada et al, 2011). An inflammatory response, i.e., the upregulation of IL-1β, is also observed in the glia and RGCs after NMDA administration, suggesting the involvement of inflammation in response to excitotoxicity.…”
Section: Cell Body Injurymentioning
confidence: 99%
“…Immunoblot analysis was carried out as described previously. 49,50 Briefly, 2-5 mg of protein was separated on a 12.5% SDS-polyacrylamide gel and transferred to the polyvinylidene membrane (Millipore, Bedford, MA, USA). After blocking with 5% nonfat milk, the membranes were incubated with primary polyclonal antibodies against Txnip (Zymed Laboratories, San …”
Section: Immunoblot Analysismentioning
confidence: 99%